Studi Evaluasi dan Pengembangan Jaringan Distribusi Air Bersih PDAM Kota Malang pada Kecamatan Kedungkandang - Chairil Shaleh; Afrenia Dewi Angguntiana (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2016)
Clean water is a basic need for humans to get priority in the handling and fulfillment. To meet these needs should be evaluated and the development of clean water needs of the community so that optimally fulfilled. The purpose of this study is that calculates water requirements in the study area and plan the development of clean water distribution network system in the District Kedungkandang, to support the planning process pipelines are needed appropriate software tools that Waternet ver DEM09, this program serves to analyze the flow of water flowing in the pipeline and can determine the pressure in each pipe. Evaluation results show an increase in the service of PDAM Malang to the subdistrict. Kedungkandang of 72% (service in 2013) became 81.9% (Service 2024). By using geometric regression analysis, the projected number Kedungkandang District residents in 2024 reached 194 801 inhabitants. With the need for clean water that reaches the average 282.6 liters / sec, the distribution of water using gravity and pipe diameter is 25 mm - 150 mm.